KONSTRUKSI PENDIDIKAN KARAKTER DI MADRASAH BERBASIS PESANTREN - Hasan Baharun; Mahmudah Mahmudah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
This research is aimed to reveal the reality of meaning, about the portrait of character education in Islamic Senior High School of Mambaul Hikam, Tegal Siwalan, Probolinggo District, Islamic Senior High School of Riyadlus Sholihin, Kademangan, Probolinggo City and Islamic Senior High School of Wali Songo 2, Banyuanyar, Probolinggo District. The reason for choosing the three research sites is because; first, the educational institution of madrasah is successful in educating and fostering the character of learners. Secondly, the madrasah is a pesantren-based madrasah, that is, madrasah synergize with pesantren in fostering the character of the students. Third, students in the madrasah are plural and plural, both in economic, social and cultural aspects. This research use qualitative method, type of case study. The results showed that, the construction of character education in madrasah-based on pesantren is done through; Integrated character education in learning system, extracurricular activities and organization, exemplary and habituation, and intensive communication between madrasah with stakeholders